2021
DOI: 10.3389/fphar.2021.615998
|View full text |Cite
|
Sign up to set email alerts
|

Notoginsenoside R1 Improves Cerebral Ischemia/Reperfusion Injury by Promoting Neurogenesis via the BDNF/Akt/CREB Pathway

Abstract: Notoginsenoside R1 (R1), a major component isolated from P. notoginseng, is a phytoestrogen that exerts many neuroprotective effects in a rat model of ischemic stroke. However, its long-term effects on neurogenesis and neurological restoration after ischemic stroke have not been investigated. The aim of this study was to evaluate the effects of R1 on neurogenesis and long-term functional recovery after ischemic stroke. We used male Sprague-Dawley rats subjected to middle cerebral artery occlusion/reperfusion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Cerebral ischaemia–reperfusion (I/R) was induced in rats through middle cerebral artery occlusion/reperfusion (MCAO/R) by following a previously described method (Zhu et al. 2020 , 2021c ). The occlusion lasted for 2 h until reperfusion.…”
Section: Methodsmentioning
confidence: 99%
“…Cerebral ischaemia–reperfusion (I/R) was induced in rats through middle cerebral artery occlusion/reperfusion (MCAO/R) by following a previously described method (Zhu et al. 2020 , 2021c ). The occlusion lasted for 2 h until reperfusion.…”
Section: Methodsmentioning
confidence: 99%
“…Proteins were extracted using RIPA lysis buffer containing phosphatase and protease inhibitors ( 26 ). Aliquots containing the same number of proteins were separated on a 10% sodium dodecyl sulfate-polyacrylamide gel and then transferred to a PVC membrane for immunoblotting.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that the application of BDNF to visual cortical neurons increases PSD-95 delivery to dendrites and specifically binds to TrkB receptors, promoting synaptic plasticity [ 152 ]. In vivo and in vitro experiments also proved that Notoginsenoside R1 could activate Akt and enhance the expression of BDNF, including the transcriptional level of its upstream target gene CREB, so as to achieve the recovery of neurological function after stroke [ 153 ].…”
Section: Postsynaptic Effect Of Glutamate As the Main Mechanism Of Ne...mentioning
confidence: 99%